Tectonic inversion in the Caribbean-South American plate boundary: GPS geodesy, seismology, and tectonics of the Mw 6.7 22 April 1997 Tobago earthquake - Weber, John C. (2015)
On 22 April 1997 the largest earthquake recorded in the Trinidad‐Tobago segment of the Caribbean‐South American plate boundary zone (Mw 6.7) ruptured a shallow (~9 km), ENE striking (~250° azimuth), shallowly dipping (~28°) dextral‐normal fault ~10 km south of Tobago. In this study, we describe this earthquake and related foreshock and aftershock seismicity, derive coseismic offsets using GPS data, and model the fault plane and magnitude of slip for this earthquake. Coseismic slip estimated at our episodic GPS sites indicates movement of Tobago 135 ± 6 to 68 ± 6 mm NNE and subsidence of 7 ± 9 to 0 mm. This earthquake was anomalous and is of interest because (1) its large component of normal slip and ENE strike are unexpected given the active E‐W dextral shearing across the Caribbean‐South American plate boundary zone, (2) it ruptured a normal fault plane with a low (~28°) dip angle, and (3) it reactivated and inverted the preexisting Tobago terrrane‐South America ocean‐continent (thrust) boundary that formed during early Tertiary oblique plate convergence.